FAKTOR PENGHAMBAT DIGITALISASI PEMASARAN DAN KEUANGAN UMKM DI KABUPATEN SITUBONDO - Ahmat Muniril Ihsan; Moch. Nabil Quraisy; Donny Anugrah Putra; Inayatul Masruro (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Digital transformation has become a crucial driver for strengthening the competitiveness of micro, small, and medium enterprises (MSMEs) in Indonesia. Nevertheless, the process of digitalizing marketing and financial management among MSMEs in Situbondo Regency continues to face multiple structural and behavioral challenges. This study aims to analyze the key factors hindering digitalization, focusing on five main aspects: human resources and digital literacy, infrastructure and technology, the development of online marketing, local government support, and barriers to financial digitalization. A qualitative descriptive method was employed, referring to the theoretical frameworks. Data were collected through document review, and an extensive literature study from academic journals, statistical reports, and government publications. The data analysis followed the stages of reduction, presentation, and interpretation to derive an in-depth understanding of MSME digitalization barriers within the local socio-economic context. The findings reveal that low levels of digital and financial literacy, limited internet infrastructure, outdated technological devices, and the absence of consistent government mentoring programs remain the dominant obstacles to digital transformation. Furthermore, online marketing practices are still basic, and financial digitalization is constrained by limited trust in data security and inadequate knowledge of digital payment systems. These results highlight that successful digital transformation requires more than technological readiness—it demands human-capital strengthening, equitable infrastructure, continuous capacity-building, and collaborative governance involving government, academia, private sectors, and communities to foster an inclusive and sustainable MSME digital ecosystem in Situbondo Regency.